2007
DOI: 10.1016/j.cardiores.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis in atherosclerosis: Molecular mechanisms and implications for plaque progression and stability

Abstract: Macrophages play a key role in atherosclerotic plaque destabilization and rupture. In this light, selective removal of macrophages may be beneficial for plaque stability. However, macrophages are phagocytic cells and thus have an important additional role in scavenging of modified lipoproteins, unwanted or dead cells and cellular debris via phagocytosis. The concept of phagocytosis as well as the underlying mechanisms is well defined but the effect of phagocytosis in terms of plaque stability remains poorly un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
193
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(201 citation statements)
references
References 90 publications
7
193
0
1
Order By: Relevance
“…Macrophage dysfunction and accumulation initiates atherosclerosis and promotes lesion instability [45] . To determine the effect of betulin on macrophages in vivo, we performed immunofluorescence experiments on cryosections of the aortic sinus from different treatment groups of apoE -/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage dysfunction and accumulation initiates atherosclerosis and promotes lesion instability [45] . To determine the effect of betulin on macrophages in vivo, we performed immunofluorescence experiments on cryosections of the aortic sinus from different treatment groups of apoE -/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of metallic debris may be attributed to the unintended wear mechanism of impingement between the metallic endplates arising from malpositioning and/or subsidence, which was noted in more than 50% of contemporary fixed-bearing device retrievals in a separate retrieval study [20]. Interestingly, considerable amounts of hemosiderin were present in many of these tissues, indicative of phagocytosis of erythrocytes and degradation of hemoglobin by macrophages [13,32]. The exact contribution of hemosiderin to revision remains unclear; however, a previous study has associated the deposition with the accumulation of activated macrophages that are positive for osteoclastic cell markers [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that phagocytosis of apoptotic cells by lipid-loaded macrophages is severely impaired in advanced atherosclerotic lesions, resulting in accumulation of proinflammatory necrotic debris and plaque instability (23,24). Moreover, the intracellular autophagy pathway in lipid-loaded macrophages has also been shown to be impaired (25). Thus, a better understanding of how apoptosis and autophagy are being regulated in vascular lesion cells is essential.…”
mentioning
confidence: 99%